Evaluating Water Quality of Abu Zarag Marsh Using GIS Technique during the Flood Season - Ahmed Zamel Hassan; Nawar O. A. Al-Musawi (Recent Progress in Science and Technology Vol. 8, 2023)
This study focuses on the Iraqi marshes, specifically the Abu Zarag marsh located in the southern city of Al-Nasiriyah, which is considered the most significant heritage in Iraq. The research is divided into two main parts. The first part involves the evaluation of water quality parameters in Abu Zarag marsh during the flooding season from December 2018 to April 2019. The parameters include Temperature, pH, Electrical Conductivity, Total Dissolved Solids, Alkalinity, Total Hardness, Turbidity, Dissolved Oxygen, Sulfate, and Nitrate. The second part involves comparing the water quality parameters of the recent period with those of the previous years from 2014 to 2019. The research findings are presented using an Arc GIS map. Additionally, the study includes modeling and simulation of flooding during the study period using the Arc GIS-Arc Scene program. The results of the research show that the Iraqi marshes, particularly the Abu Zarag marsh, have been replenished, leading to the recovery of the natural environment in southern Iraq.